Pengaruh Karakteristik Auditor dan Kompleksitas Operasi Perusahaan terhadap Audit Report Lag: Studi Empiris Perusahaan Properti yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Audi, Monica; Fauzihardani, Eka (Universitas Negeri Padang, 2025)
This study seeks to analyse the impact of auditor gender, auditor reputation, auditor tenure and the complexity of company operations on the on audit report lag in property sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. It will also take into account the influence of company operational complexity. The duration between the end of the fiscal year and the date of the independent auditor's report signature is called the audit report lag. The premise of attribution theory underpins this investigation. Using a quantitative approach and purposive sampling, 58 property companies provided 232 firm-year observations. Using SPSS software, we performed multiple linear regression analyses on the collected data. There is a positive correlation between auditor gender and audit report lag, no correlation between auditor reputation and audit report lag, a negative correlation between audit tenure and audit report lag, and a positive correlation between auditor reputation and audit report lag and company operational complexity, according to the results.